Peningkatan Aktivitas Belajar Siswa Kelas III SD pada Pembelajaran Ilmu Pengetahuan Alam melalui Kombinasi Media Gambar dan Model di SD Negeri 02 Harau - Sukrieti, Sukrieti (Jurusan PIPS FKIP UMMY Solok, 2019)
This study is a class action research conducted in class III SDN 02 Harau. The study was conducted in the first semester of the 2017/2018 academic year. There are three cycles in this study. Data is collected through observation, tests, and field notes. The findings of this study have increased student activity from cycle one to cycle two and cycle three. Increases occur in all aspects studied. In other words the use of media images and models can improve the learning activities of third grade students at SDN 02 Harau in learning Natural Sciences. The result of this research was learning implementation by combining picture as media and learning model in IPA subject could increase students’ learning activities at Grade III of SD Negeri 02 Harau.